2003
DOI: 10.1055/s-2003-38767
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Follow-Up of Patients with Endoscopic Treatment of Sporadic Adenomas of the Papilla of Vater

Abstract: Long-term follow-up revealed no case of advanced ampullary cancer and suggested that endoscopic treatment was satisfactory for the large majority of patients with ampullary adenomas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
35
1
5

Year Published

2004
2004
2015
2015

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 165 publications
(43 citation statements)
references
References 14 publications
2
35
1
5
Order By: Relevance
“…In 58/283 patients (20%), however, no method succeeded in locating the source of OGIB. Our results support the findings of others who showed that CE could also identify pathologies that had been missed at gastroscopy or colonoscopy [10,11,12,13,14,15,34,35,36,37,38,39]. …”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…In 58/283 patients (20%), however, no method succeeded in locating the source of OGIB. Our results support the findings of others who showed that CE could also identify pathologies that had been missed at gastroscopy or colonoscopy [10,11,12,13,14,15,34,35,36,37,38,39]. …”
Section: Discussionsupporting
confidence: 92%
“…Our clinical data show a high diagnostic yield (72%) of CE compared to recently published studies that showed the diagnostic yield to vary from 32 to 76% [10,11,12, 15, 35, 39]. This difference may be explained, at least in part, by the relatively small size of the other studies (approximately 20–60 patients in each).…”
Section: Discussioncontrasting
confidence: 56%
See 2 more Smart Citations
“…Currently CE is being used to evaluate GI bleeding of obscure origin, small-bowel pathology such as polyposis syndromes, inflammatory and infiltrative small-bowel disorders [1,2,3,4]. CE has been compared with push enteroscopy in the evaluation of small-bowel lesions and it has been found to be a better modality [5,6,7,8]. The superior performance of CE is probably due to the fact that it can deliver detailed images of the mucosa because of its closer proximity to the mucosal wall, thereby distinguishing smaller lesions, including those between the folds.…”
Section: Introductionmentioning
confidence: 99%